Transfer of Advanced Technologies as Basis for the Recovery of Ukraine’s Economy - Novikov, M.V. (Science and Innovation, 2024)
The economy of Ukraine has no prospects for recovery unless a huge accumulated potential of R&D works of Ukrainian scholars and researchers are widely implemented in the industrial and social fields. The success thereof depends on the organization and facilitation of the public private partnership at different levels: from the government to the institutions of the NAS of Ukraine.